Arus Komunikasi Organisasi Public Relations Kantor Wilayah Direktorat Jenderal Pajak Sulawesi Selatan, Barat dan Tenggara Perspektif Islam - Delila Terida Yoku; Arianto (KOMUNIDA : Media Komunikasi dan Dakwah, 2022)
This research aims yo find out and analyze the communication flow of the public relations organization of the Regional Office of the Directorate General of Taxes in South, West and Southeast Sulawesi based on an Islamic perspective. The method used in this study uses qualitative methods, data collection is done by means of interviews, observation, and documentation. The results of this study showed that the flow of public relations communication in the organization of the Regional Office of the Directorate General of Taxes of South, West and Southeast Sulawesi in the perspective of Islamic flow shows four directions of information or messages in organizational communication at the Regional Office of the Directorate General of Taxes of South, West and Southeast Sulawesi. The downward flow of organizational communication, the upward flow of organizational communication, the lateral flow of organizational communication, and the flow of cross-channel communication are information flows carried out by the Public Relations of the Directorate General of Taxes of South, West and Southeast Sulawesi in creating harmonious relationships and synergistic cooperation. The principles of effective communication are qaulan syahid, qaulan maysurah, qaulan baligha, qaulan karimah, qaulan layyinah, and qaulan Ma'ruf. Public Relations of the Directorate General of Taxes of South, West and Southeast Sulawesi can adjust the method of communication from an Islamic perspective according to the type of information to be conveyed. Public Relations acts as a communicator as well as a mediator in an organization, including the Directorate General of Taxes for South, West and Southeast Sulawesi.